2003
DOI: 10.1254/jphs.92.259
|View full text |Cite
|
Sign up to set email alerts
|

Orexin Receptor Type-1 Couples Exclusively to Pertussis Toxin-Insensitive G-Proteins, While Orexin Receptor Type-2 Couples to Both Pertussis Toxin-Sensitive and -Insensitive G-Proteins

Abstract: Signal transduction pathways of orexin receptors were examined using a nerve-like cell line transfected with orexin receptor type-1 (OX1R) and orexin receptor type-2 (OX2R). Forskolin-stimulated cyclic adenosine 3,5-monophosphate (cAMP) accumulation in OX2R-expressing cells was inhibited by orexin in a dose-dependent manner, and the effect was abolished by pretreatment with pertussis toxin (PTX). The inhibitory effect of orexin on forskolin-stimulated cAMP accumulation was not observed in OX1R-expressing cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 27 publications
(30 reference statements)
3
98
0
1
Order By: Relevance
“…This suggests the activation of nonselective cation channels downstream of OX2R. The activation of phospholipase C by the ␤␥ subunit of the G-protein might be involved because OX2R is believed to couple with the Gq and Gi types of G-proteins (Zhu et al, 2003). We previously showed that orexin neurons are activated by CCK and AVP via the G-protein-coupled receptors (Gq), CCK A receptor, and the V1a receptor (Tsujino et al, 2005;Tsunematsu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the activation of nonselective cation channels downstream of OX2R. The activation of phospholipase C by the ␤␥ subunit of the G-protein might be involved because OX2R is believed to couple with the Gq and Gi types of G-proteins (Zhu et al, 2003). We previously showed that orexin neurons are activated by CCK and AVP via the G-protein-coupled receptors (Gq), CCK A receptor, and the V1a receptor (Tsujino et al, 2005;Tsunematsu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is frequently observed in heterologous expression systems with both OX 1 R and OX 2 R (Smart et al, 1999;Holmqvist et al, 2002;Ammoun et al, 2003) and is likely to be a consequence of activation of phospholipase C (PLC) and the generation of IP 3 . Some studies on native receptors in neurons have demonstrated sensitivity to inhibitors of phosphatidylinositol-specific PLC (Zhu et al, 2003;Muroya et al, 2004), suggesting that some store release may take place. Conversely, a Ca 2ϩ release from intracellular stores has not been demonstrated in native neurons although explicitly tested for Kohlmeier et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Orexin is typically thought to have excitatory depolarization effects on neurons (Korotkova et al, 2003;Marcus et al, 2001;Sakurai et al, 1998;Trivedi et al, 1998;van den Pol et al, 2002;Zhu et al, 2003). However, neurons in NAc may exclusively contain orexin-2 receptors (OX r 2) (Ch'ng and Lawrence, 2015; Trivedi et al, 1998), which can be coupled with either Gi or Gq subunits, and may inhibit neurons via the augmentation of inhibitory GABA signals (Martin et al, 2002;Zhu et al, 2003). If so, neuronal inhibition by orexin could be more similar to GABAergic hyperpolarizations or Gi-coupled opioid or endocannabinoid signaling.…”
Section: Orexin Rostral Hotspotmentioning
confidence: 99%